Annealing Effects on GaAs/Ge Solar Cell after 150 keV Proton Irradiation - Meihua Fang; Tao Fei; Mengying Bai; Yipan Guo; Jingpeng Lv; Ronghui Quan; Hongbo Lu; Huiping Liu (International Journal of Photoenergy)
Radiation-induced defects are responsible for solar cell degradation. The effects of radiation and annealing on the defects of a GaAs/Ge solar cell are modeled and analyzed in this paper. The electrical performance and spectral response of solar cells irradiated with 150 keV proton are examined. Then, thermal annealing was carried out at 120°C. We found that the proportion of defect recovery after annealing decreases with increasing irradiation fluence. The minority carrier lifetime increases with decreasing defect concentration, which means that the electrical performance of the solar cell is improved. We calculated the defect concentration and minority carrier lifetime with numerical simulation and modeled an improved annealing kinetic equation with experimental results.